2021
DOI: 10.1038/s41598-021-01872-5
|View full text |Cite
|
Sign up to set email alerts
|

Field metabolic rates of giant pandas reveal energetic adaptations

Abstract: Knowledge of energy expenditure informs conservation managers for long term plans for endangered species health and habitat suitability. We measured field metabolic rate (FMR) of free-roaming giant pandas in large enclosures in a nature reserve using the doubly labeled water method. Giant pandas in zoo like enclosures had a similar FMR (14,182 kJ/day) to giant pandas in larger field enclosures (13,280 kJ/day). In winter, giant pandas raised their metabolic rates when living at − 2.4 °C (36,108 kJ/day) indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Our team is developing a program to release captive-bred giant pandas into the wild by adopting the Human-Assisted Soft Release Method. Through this method, our investigators can examine the trained giant pandas and collect more data in the wild without undergoing anesthesia [ 19 , 40 ]. A total of eight adult ticks were collected from the body surface of our wild-training giant pandas living in Yingjing Area of Giant Panda National Park (102°19′30″ E–102°57′0″ E, 29°28′30″ N–29°57′0″ N) from March to April 2022, and stored in 95% ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Our team is developing a program to release captive-bred giant pandas into the wild by adopting the Human-Assisted Soft Release Method. Through this method, our investigators can examine the trained giant pandas and collect more data in the wild without undergoing anesthesia [ 19 , 40 ]. A total of eight adult ticks were collected from the body surface of our wild-training giant pandas living in Yingjing Area of Giant Panda National Park (102°19′30″ E–102°57′0″ E, 29°28′30″ N–29°57′0″ N) from March to April 2022, and stored in 95% ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…One group reported that giant pandas have DEE (41 ± 12 kcal/kg 0.75 /day) similar to the three-toed sloth ( Bradypus variegatus ) and, therefore, much lower than virtually all other terrestrial mammals, including koalas ( Phascolarctos cinereus ) and echidnas ( Tachyglossus aculeatus ) 4 . Those results were contradicted by others who reported DEE three times higher (122 ± 51 kcal/kg 0.75 /day) 5 , 6 . Although housing and diets varied from captive to free-ranging and from only bamboo to mixtures of bamboo and human-type foods, neither group suggested or reported major differences in DEE due to diet or housing 4 6 .…”
Section: Introductionmentioning
confidence: 56%
“…Although housing and diets varied from captive to free-ranging and from only bamboo to mixtures of bamboo and human-type foods, neither group suggested or reported major differences in DEE due to diet or housing 4 6 . However, the latter group 5 , 6 suggested that differences in activity might explain the differences in DEE within giant pandas and between giant pandas and other ursids, but that idea was not tested beyond noting that polar bears would have greater energy expenditures for travel and, potentially, thermoregulation than giant pandas 6 .…”
Section: Introductionmentioning
confidence: 98%
“…Reactive oxygen species and heat shock proteins both play integral roles in the heat‐stress response (Paital, 2016; Pires et al, 2019) and might serve as indicators of thermoregulatory function. Likewise, measurement of metabolic rates in the field, while difficult, has proven useful for some mammals (Bi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%